An Analysis of Risk Factors Contributing to Nutritional Problems and Stress among Students at the “X” Islamic Boarding School, Sidoarjo - Zamzam, Maki Zamzam (Universitas Nahdlatul Ulama Surabaya, 2025)
Students at the “X” Islamic Boarding School in Sidoarjo face nutritional problems (deficiency or excess) and stress due to academic burden, strict rules, and adaptation to a new environment. This study investigated the multifaceted relationship between nutritional intake, physical activity, nutritional knowledge, social support, counseling guidance, coping strategies, and stress levels about the nutritional status of students aged 13–17 years (n = 91) using a cross-sectional design. Data were collected through a structured questionnaire that measured academic burden, social pressure, social support, counseling services, coping success, nutritional knowledge, peer support, self-efficacy in choosing food, eating patterns, and anthropometric measurements (weight, height, and BMI/Age). Bivariate analysis revealed that academic burden (p < 0.001), social support (p = 0.035), counseling guidance (p = 0.011), and coping (p = 0.015) were significantly associated with stress, while social pressure was not (p = 0.611). Stress significantly influenced nutritional status (p=0.001), while nutritional knowledge (p=0.013), peer support (p=0.002), self-efficacy (p=0.014), and dietary patterns (p<0.001) were significantly correlated with nutritional status. In conclusion, psychosocial factors and nutritional behavior simultaneously influence the physical and mental well-being of students, so a comprehensive strategy is needed to improve student well-being that includes academic management, strengthening social support, counseling services, increasing knowledge and coping, and dietary education. Keywords: students, nutritional problems, stress, Islamic boarding schools